Neue Ansätze der Visualisierung der Stadt-Umland-Problematik: Dargestellt auf der Grundlage einer vergleichenden Betrachtung der Urban-Sprawl-Diskussion in den USA und Deutschland - Wolf, Sabine; Hagedorn, Carsten (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
The article presents new ways of visualising problematic suburban developments. After reflecting on the dealing with peripheral growth in the US and Germany, possible future developments of space in an exemplary region are simulated by means of computer graphics. The advantage of this process lies in the number of different graphical results in one scenario after accessing the system. There is no firm development stipulated. Rather, different possible developments are shown.